Sensorless control of induction motors - Hu, Jun. (2008)
Mechanical speed measurement used to be an undesired necessity for closed-loop inverter-fed induction machines. When the vector control, which does not need a speed signal from a mechanical speed sensor, is applied to an inverter-fed induction motor, it is possible to improve the control performance and to reduce the cost of the control equipment in many industrial application.